Pengaruh Harga, Kualitas Pelayanan dan Kepercayaan terhadap Keputusan Penggunaan Jasa Transportasi Online Go-Car dengan Kepuasan Konsumen Menjadi Moderasi pada Saat Kondisi Pandemi Covid 19 di Kota Tangsel - Ravindra Safitra (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of price, service quality, consumer trust on usage decisions with customer satisfaction as a moderation for online transportation services, in this case Go Car. The population in this study are all customers who have used Go Car online transportation services. The sampling technique in this study was accidental sampling or accidental sampling so that there were 95 respondents. This study uses statistical tools, namely SmartPLS and Microsoft Excel as tabulation data processing. The results showed that during a pandemic, people chose to stay at home, and would only travel in very important conditions. So that consumer trust is one of the factors that can influence the decision to use Go Car online transportation services